Pre-emptive BioGlue priming of the branched Evita Open NEO hybrid prosthesis: tackling excessive oozing. (4th September 2021) - Ho, Jacky Y K; Lim, Kevin; Fujikawa, Takuya; Wong, Randolph H L
Abstract: Excessive oozing after total arch replacement with the frozen elephant trunk technique through the fabric of the E-vita Open NEO raised concern about its early adaptation. The mechanism is speculated to be multifactorial. Our goal was to report our approach using pre-emptive BioGlue priming on the fabric against the oozing phenomenon. Abstract : Haemostasis in open aortic surgery is determined by multiple factors.